Elements per a una sociologia sistèmica del llenguatge - Conill, Josep J.; Salomé, Anna (Caplletra. Revista Internacional de Filologia, 2004)
This article outlines the basic principles for a general sociology of language witha systematic purpose, and questions several aspects of the dominant “common sense”. The work of the German sociologist Niklas Luhmann (1927–1998) is used as a starter point. The authors explain Luhmann’s thinking, who understands the social system as a complex fruit of communication, autoreferential as well as autopoetical. The article shows the analytical deficiencies of Catalan sociolinguistics, limited to the study of the most basic systematic levels and suggests a more global theoretical perspective.